2017
DOI: 10.1007/s13349-017-0229-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved axle detection for bridge weigh-in-motion systems using fiber optic sensors

Abstract: Bridge weigh-in-motion (B-WIM) systems provide a non-destructive means of gathering traffic loading information by using an existing bridge as a weighing scale to determine the weights of vehicles passing over. In this research critical locations for sensors for the next-generation B-WIM were determined from a full 3D explicit finite element analysis (FEA) model. Although fiber optic sensors (FOS) have become increasingly popular in SHM systems there are currently no commercially available fiber optic WIM syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 16 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Bridge WIM is an SHM method to reconstruct the loading information of a bridge structure by determining the weight of the passing over vehicles [77]. Lydon et al [128,129] used fiber optic sensors for axle detection on an reinforced concrete bridge in Northern Ireland. The results confirmed the performance of the fiber optic sensors for gathering traffic loading information.…”
Section: Vehicle-classification-based Methodsmentioning
confidence: 99%
“…Bridge WIM is an SHM method to reconstruct the loading information of a bridge structure by determining the weight of the passing over vehicles [77]. Lydon et al [128,129] used fiber optic sensors for axle detection on an reinforced concrete bridge in Northern Ireland. The results confirmed the performance of the fiber optic sensors for gathering traffic loading information.…”
Section: Vehicle-classification-based Methodsmentioning
confidence: 99%
“…WhenFBG is subjected to external factorssuch as pressure, vibration, temperature, stress and strain, refractive index and grating period varies, there will be corresponding changes in the reflected wavelength. Since the parameter of measurement is the wavelength of light which is not affected by electromagnetic fields, the process is immune to electromagnetic interference and hence is intrinsically more stable than any electrical monitoring system as explained in [6]. The reflected wavelength can be calculated as…”
Section: Fiber Bragg Gratingmentioning
confidence: 99%
“…Kalhori et al (2017) found out in their field test that shear strain sensors installed close to the support were able to detect even closely spaced axles reliably. Another method suggested by Lydon et al (2017) utilised compressive strain measurements in the girder for the axle detection. The strain sensors were installed to the girder of the bridge so that it could measure the compressive strains (Figure 15 (b)) caused by the vehicle.…”
Section: Axle Detectionmentioning
confidence: 99%